Reeducación psicomotriz para la disgrafía caligráfica, en los estudiantes de 5to año de educación general básica, de la unidad educativa José Ángel Palacio de la ciudad de Loja. - Sisalima Calva, Vanessa Elizabeth (2018)
The present work entitled: PSYCHOMOTRIZ REEDUCATION FOR THE CALIGRAPHIC DISGRAPHY, IN THE STUDENTS OF 5TH YEAR OF BASIC GENERAL EDUCATION, OF THE EDUCATIONAL UNIT "JOSÉ ÁNGEL PALACIO" OF THE CITY OF LOJA, was carried out in the students who presented errors in the form and tracing of writing, and was developed with the main objective of diminishing calligraphic dysgraphia through a proposal of psychomotor reeducation. The approach is quali-quantitative; since it is based on descriptive and explanatory designs; the process that was used is located in three phases: theoretical-diagnostic, design-planning of the proposal and evaluation-evaluation of it, for it was used the scientific method, pre-experimental, analytical-synthetic, inductivedeductive, descriptive; techniques such as: observation, the writing subtest of TALE. The sample is of a non-probabilistic type corresponding to 20 students. The analysis of the variables allowed to organize the results where the sample investigated, presented errors of form and layout of the writing, mainly in the indicators of body posture, grasp of the pencil and speed in its entirety, as well as a large proportion in the interlineation indicator. It was concluded that the application of the proposal significantly reduced the problems encountered, that is, the guarantee of the proposal contributed to only a small percentage of the students maintaining errors in these indicators. And in the case of line spacing, a small improvement was achieved. It is for this reason that to avoid errors of form and layout of the writing it is necessary that from the initial education the teachers carry out playful activities, of corporal expression, laterality, spatial and temporal notion, coordination, and correct the corporal posture, grasp of the pencil.